2014
DOI: 10.1371/journal.pone.0112433
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Duration and Childhood Obesity: Cross-Sectional Analysis in Peru and Patterns in Four Developing Countries

Abstract: BackgroundWe aimed to describe the patterns of nutritional status and sleep duration in children from Ethiopia, India, Peru and Vietnam; to assess the association between short sleep duration and overweight and obesity, and if this was similar among boys and girls in Peru.Methods and FindingsAnalysis of the Young Lives Study, younger cohort, third round. In Ethiopia there were 1,999 observations, 2,011, 2,052 and 2,000 in India, Peru and Vietnam, respectively. Analyses included participants with complete data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 34 publications
2
28
0
6
Order By: Relevance
“…Of note, our results indicated that the association was modified by gender. Previous studies observed that gender was an effect modifier of the association between short sleep duration and overweight among children [21]. A possible explanation is that females cope better with environmental stress, and thus they would need a much shorter sleep duration to put them at a risk of overweight or obesity [22,23].…”
Section: Discussionmentioning
confidence: 97%
“…Of note, our results indicated that the association was modified by gender. Previous studies observed that gender was an effect modifier of the association between short sleep duration and overweight among children [21]. A possible explanation is that females cope better with environmental stress, and thus they would need a much shorter sleep duration to put them at a risk of overweight or obesity [22,23].…”
Section: Discussionmentioning
confidence: 97%
“…Si se considera la relación obesidad/sueño, CarrilloLarco et al 14 demostraron que la obesidad era un 64,0% más frecuente entre los niños con sueño de corta duración, lo que explicaría lo anteriormente descrito. Una revisión sistemática de 10 estudios realizados entre el año 2002 y 2014 reportaron una asociación positiva entre la corta duración del sueño y el riesgo de padecer obesidad, en niños en edad escolar, encontrándose un aumento de riesgo de padecer obesidad, de hasta 3 veces mayor en niños que duermen menos de 9 horas/ noche 15 .…”
Section: Bajounclassified
“…Included studies were from 18 countries with a total population of 225,022 children (range from 207 to 66,817 children; Table ). Samples were recruited from preschools and schools in 25 (Altenburg et al., ; Amaral et al., ; Bawazeer et al., ; Bel et al., ; Bernier et al., ; Biggs et al., ; Bornhorst et al., ; Cao et al., ; Chaput & Janssen, ; Danielsen et al., ; De Jong et al., ; Eisenmann, Ekkekakis, & Holmes, ; Franckle et al., ; Hayley et al., ; Hense et al., ; Hysing, Sivertsen, Garthus‐Niegel, & Eberhard‐Gran, ; Kjeldsen et al., ; Kuciene & Dulskiene, ; Lam, ; Lam & Yang, ; Leger, Beck, Richard, & Godeau, ; Li et al., , ; Morrissey et al., ; Ozturk et al., ; Taveras, Rifas‐Shiman, Oken, Gunderson, & Gillman, ; Wu et al., ), the general population in three (Lee & Park, ; Roberts & Duong, ; Shi et al., ), healthcare settings in three (Bathory et al., ; Halal et al., ; Taveras et al., ), and was not reported in seven studies (Bonuck, Chervin, & Howe, ; Carrillo‐Larco, Bernabe‐Ortiz, & Miranda, ; De Heredia et al., ; Fisher et al., ; Garaulet et al., ; Javaheri et al., ; McDonald et al., ). Some cohorts were reported in more than one article, and it is possible that the same data were used in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The methods used to establish an applied cut‐off regarding normal versus abnormal sleep duration were also varied. Examination of sleep was reported either as total sleep in 24 hr (Bawazeer et al., ; Bornhorst et al., ; Franckle et al., ; Garaulet et al., ; Kuciene & Dulskiene, ; Lee & Park, ; Li et al., ; Ozturk et al., ; Shi et al., ; Taveras et al., ; Wu et al., ) or as sleep occurring at night (Altenburg et al., ; Amaral et al., ; Bathory et al., ; Bel et al., ; Biggs et al., ; Bonuck et al., ; Cao et al., ; Carrillo‐Larco et al., ; Chaput & Janssen, ; Danielsen et al., ; De Heredia et al., ; De Jong et al., ; Eisenmann et al., ; Fisher et al., ; Halal et al., ; Hayley et al., ; Hense et al., ; Hysing et al., ; Javaheri et al., ; Kjeldsen et al., ; Lam, ; Lam & Yang, ; Leger et al., ; Li et al., ; McDonald et al., ; Morrissey et al., ; Roberts & Duong, ). Daytime napping was presented by some studies, but was only included in the total sleep duration in a portion of these articles (Bathory et al., ; Biggs et al., ; Bornhorst et al., ; Fisher et al., ; Kuciene & Dulskiene, ; Lam & Yang, ; Li et al., ; Taveras et al., ).…”
Section: Resultsmentioning
confidence: 99%